KAP Study of Street Food Vendors on Food Safety in Selected Areas of Pune (International Journal of Food and Nutritional Sciences, 2024)
Food is essential to life hence food hygiene is the primarily important maintain food safety. As the growing world people are more attentive to save the time by various ways, one of the majors is moving towards fast food or street foods. Street food is made from food and drink prepared, for consumption, prepared and sold on the street or in other public places such as markets and/or exhibitions, often sold on counters or through temporary vans and carts street vendors. Food hygiene is a set of food manufacturing practices that aim to minimize biological food hazards through safe and clean operations to protect public health from foodborne diseases. This study was about food hygiene knowledge, attitude, and practices among street food vendors, an offline survey in Pune city Maharashtra, with face-to-face interview considering standardized questionnaire with undertaking some socio-demographic characteristic (Gender, age, vending experience, etc.) respectively. The obtained data were computed to determine the knowledge regarding various factors in respondents. This study shows that street vendors had excellent knowledge about food safety which is 100% and a good attitude toward food hygiene which is 64.84 % as well as they have good food hygiene practices which is 75.73 %.